Pregerminative Treatments to Improve Germination of Plant Species with Forage Potential in Conditions of the Colombian Amazonian Foothills - Juan Pablo Narváez-Herrera; Joaquín Angulo-Arizala; Wilson Barragán-Hernández; Liliana Mahecha-Ledesma (International Journal of Agronomy)
The research aimed to evaluate the germination of seeds of four forage species present in the Colombian Amazonian foothills, the speed of germination and the selection indices of Erythrina poeppigiana (EP), Guazuma ulmifolia (GU), Clitoria fairchildiana (CF), and Piptocoma discolor (PD) under nursery conditions, through a randomized complete block design with five repetitions and three pregerminative treatments, T0 (control): immersion in water for 24 h, T1: 24 h in water followed by 3 minutes in water at 80°C, and T2: 24 h in a solution of 600 mg/L of gibberellic acid (GA3) followed by 1 minute in water at 80°C. Additionally, GU seeds underwent mechanical scarification. In total, 750 seeds per species were used, resulting in 3,000 seeds in the experiment. An analysis of variance and a Tukey’s mean comparison test were performed for the variable proportion of germinated seeds, germination speed, and selection indices among treatments. Germination curves were analyzed using two growth models: logistic and Gompertz. The results of these models were evaluated based on Akaike (AIC), Bayesian (BIC), and R2 statistical criteria, with the Gompertz model selected for its better fit and biological interpretation of the data. The T2 treatment in EP recorded the highest germination with 88.8 ± 1.36% different (p<0.05) from the results obtained in T1 79.6 ± 1.22% and the control 61.6 ± 0.94%, the previous treatments in CF had no effect, the control in this species was the best with 68.8 ± 2.94% as in the GU seeds, T1 presented a germination of 78.8 ± 6.21% equal to T2 73.6 ± 5.80% and different (p<0.05) to the control 25.2 ± 2.01% highlighting the positive effect of manual scarification. PD seeds began germination after 25 days of experimentation, suggesting that this species requires a more extended experimental period. Under Amazonian foothill conditions, EP and GU seeds respond well to 24-hour hydration and the addition of 600 mg of GA3; however, this dose may be excessive for PD and CF seeds.